ANALISIS FAKTOR YANG MEMPENGARUHI GENERASI Z MENYALURKAN INFAK MELALUI E-COMMERCE - Gigih, Gigih Aji Nugroho; Aminullah Achmad Muttaqin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Indonesia is a country with a Muslim population and the highest level of generosity in the world. One of the things that includes philanthropic activities is infaq. BAZNAS as the regulator of ZIS in Indonesia innovates by inviting e-commerce and crowdfunding to work together to increase infaq collection. Evidently, infaq collection has increased. This study aims to analyze the factors that influence Generation Z to distribute infaq through e-commerce Tokopedia. The research method used is quantitative by using exploratory factor analysis. The research object selected was Generation Z in Malang City who had distributed infaq through e-commerce Tokopedia. The results of this study shows that there are five factors formed from 26 indicators, namely Ease Of Use, Infak Knowledge, Altruism, Trust, and Obedience.